Penerapan IoT Dalam Pembuatan Tempat Sampah Otomatis Berbasis Microkontroler Ardiuno - Cica Umiditiya; Muhammad Feardy Casnur; Devy Kusrini (Prosiding Seminar Nasional Teknoka, 2023)
The environment is one of the most important things in life. A dirty environment and scattered rubbish can have a bad impact on humans. Usually, the trash can does not close or open automatically and the trash can is dirty. Moreover, this incident occurred because of factors that stimulate humans to throw rubbish in the right place. This is a mastermind in increasing or not realizing how to keep the world clean, sometimes an innovative approach is needed to attract everyone's attention, thereby eliminating the reluctance to throw rubbish in the right location. Trash cans can be equipped with an Internet of Things (IoT) technology system to make it easier to dispose of waste properly and benefit the community. Using an Ardiouno microcontroller, ultrasonic sensor and servo motor, the lid of this trash can can be opened automatically. The aim of this research is to develop an innovative device, namely a distinctive and attractive trash container, with the ability to open and close independently when detecting movement and knowing whether the trash can is full or not. It is hoped that this gadget can effectively attract people's attention and encourage them to throw away rubbish in the right place. The results of measuring ultrasonic sensor distance data specifically for Servo motors if it detects the condition of an object approaching with a distance data value < 10 cm, then it will activate the Servo motor to start the movement to open and close the trash cover again automatically. Meanwhile, the results of measuring ultra sonic sensor distance data specifically for traffic LEDs if >= 0 cm to <= 7 cm are red, if >= 8 cm to <= 17 cm are yellow, and <18 cm are green.